THE POLITICS OF VEILING (A STUDY OF HIJAB AND FEMALE MUSLIM IDENTITY REPRESENTATION IN INDONESIA) - Maurisa Zinira (Islamic Studies Journal for Social Transformation, 2017)
The increased number of hijabi women (women who wear hijab) in Indonesia presents changes in religioussocio-political lanscape of Muslim community in Indonesia. For hijabi, hijab is a technology for the self. It represents one’s identity through performance. Beside religious identity, hijab does explain hijabi’s social and economic status in the society. Especially with the growth of hijab industry, hijab becomes part of lifestyle. Tradition has now developed more into fashion. There emerge several hijab communities initiated by young hijabis to promote hijab trough popular culture. Looking through the phenomenon of hijab from this lense, it could be argued that hijab does not necessarily express hijabi’s religiosity and spirituality. Given certain contexts and meanings, each hijab style explains hijabi’s identity becoming instead of identity being. This paper discusses hijab focusing on two main concerns; first discussion relates to hijab and identity formation and the second relates to hijab and regulation of women’s bodies.